STRUCTURAL AND MINERALISATION MAPPING OF MUSCOVITE ORE DEPOSITS IN ELEEKU, SOUTHWESTERN NIGERIA - Magaji, Yusuf; Folorunso, Ismaeel O.; Salaudeen, Salaudeen A.; Olajide, Temitayo Adenike; Folorunsho, Owolabi Wahab (FUDMA Journal of Sciences, 2025)
Aeromagnetic data has been successfully adopted to characterise mica mineralisation for industrial purposes in Eleeku, Nigeria. The data, sheet 223-Ilorin on a scale of 1:100,000 were obtained from the Nigerian Geological Survey Agency (NGSA) at a height of 80 meters along a series of NE-SW flight lines spaced 500 m interval. The Total Magnetic Intensity data was gridded at 125 m then reduction to the magnetic equator (RTE) was applied to center magnetic anomalies over their respective magnetic source bodies with the aid of Oasis Montaj™ software. Other enhancement techniques applied are total horizontal gradient (THG), tilt angular derivative (TDR) and 3-D Euler deconvolution. The results of the highest peak of THG on zero TDR in addition to 3D Euler deconvolution serve as source edge detection of geologic structures responsible for hosting mineralisation. 15 faults oriented in NW-SE and NE-SW directions were discovered. 4 out of these 15 are carriers of muscovite bearing faults, with a maximum depth of approximately 600 m and dip angles varying between 650 and 820. 3D Euler deconvolution of 0 structural index at a grid cell of 125 m and a window size 16x16 helped determine depth, position and contact between two lithologies of different magnetic source bodies. The maximum depths and dip angles to the top of the source bodies ranging between 450m - 1200 m and 650 - 820 respectively were found in Gudugba and Aboto Alfa communities while the shallow source depths and dip angles ranges from 300 - 400 m and...